PEMBERDAYAAN PELAKU USAHA EKONOMI KREATIF OLEH DINAS PARIWISATA, KEBUDAYAAN, KEPEMUDAAN DAN OLAHRAGA KABUPATEN SUMEDANG - Arip Firmansyah (JRPA - Journal of Regional Public Administration, 2026)
The purpose of this study is to find out the Empowerment of creativeeconomy business actors by Departement of Tourism, Culture, Youth,and Sports (DISPARBUDPORA). The research method used in thisstudy is purposive sampling. With research informants, namely theHead of Creative Affairs, the tourism and creative economy adyatamayoung experts, and the compiler of creativity and innovation programs.The data collection techniques used are literature studies and fieldstudies consisting of observation, interviews, and documentation.Meanwhile, the data processing procedures in this study are datareduction, data display, depiction/verification of data conclusions andtriangulation. Based on the results of the study, it is concluded that theempowerment of creative economy business actors by the SumedangRegency Tourism, Culture, Youth and Sports Office has been carriedout appropriately and in a targeted manner, but limited humanresources, lack of understanding of technology and markets, and weakleadership in the mentoring process are obstacles in the empowermentprocess. To overcome these obstacles, Departement of Tourism,Culture, Youth, and Sports (DISPARBUDPORA) has implemented astrategy of enablement through access and infrastructure development,strengthening through technical training, and support in the form ofaccess to funding, business incubation, and product promotion.